Examining Student Perception and Enthusiasm for The MBKM Program: A Comprehensive Study - Najib, Khotim Hanifudin; Ardhian, Trio; Nofrida, Eka Ridha (el-Tarbawi, 2024)
Merdeka Belajar Kampus Merdeka (MBKM) is a new policy that has not been widely understood by students. It is necessary to assess students' perceptions and interests in this policy. This study was conducted to determine the extent of student perceptions of this policy and the level of student interest in the programs offered. The stages of the research method carried out include the preparation stage, data collection stage, data processing stage, and data analysis stage. The research method used in this study is a survey method using questionnaires as a data collection tool. The respondents of this study were 232 students of the elementary school teacher education study program starting from the Class of 2020 until 2022. Data analysis techniques use descriptive analysis, categorization and cross-tabulation as well as spherman rank correlation analysis. The results showed that students' interest in participating in the MBKM program was in the medium category. Student perceptions of MBKM policies are highest in the good category, and these perceptions are related to interest in participating in the MBKM program. Meanwhile, students' perceptions of MBKM programs are in the good category and these perceptions are related to their interest in participating in the MBKM program.